Toxic Elements from Critical Raw Materials Group in Ripe and Unripe Tomatoes in A Contaminated Area: Accumulation and Potential Health Risk Assessment - Topal, Murat; Topal, E.ışıl Arslan; Öbek, Erdal (My University, 2023)
Accumulation and health risk assessment of cobalt (Co), antimony (Sb), vanadium (V), and lanthanum (La) in tomatoes growing in an area contaminated with municipal wastewater were investigated. For this aim, tomatoe samples were taken and sepertaed into root, stem and leaf parts. Co, Sb, V and La concentrations were detected in plant organs. The arrangement of the elements in the root, stem, and leaf of ripe and unripe tomatoes was V>Co>La>Sb. According to total element values in the ripe and unripe tomatoes; the highest values were 23±1.1 mg/kg and 35±1.7 mg/kg for V, respectively. Co, Sb, V, and La values accumulated by ripe and unripe tomatoes were determined as 24.65 and 25.6 times for Co, 1.8 and 2.7 times for Sb, 46 and 70 times for V and 4.4 and 6.15 times for La, respectively when compared with control. Total Co, Sb, V, and La were male
Keywords: Wastewater; health risk; tomatoes; Accumulation; non-carcinogenic